Developing a Rational Policy on Plagiarism for Institutions of Higher Education: A Case of Gulu University - Ongaya, Kizito; Alidri, Agatha; Onen, Walter Yagos; Odongkara, Beatrice; Okumu, Charles (https://doi.org/10.37284/eajes.7.3.2114, 2024)
Globally, plagiarism is a pervasive issue in institutions of higher education, posing challenges to academic integrity and ethical standards. Developing a policy on plagiarism is crucial for maintaining the quality and credibility of academic work within these institutions. The purpose of this paper is to discuss the development of a rational policy on plagiarism. The following are the objectives; to benchmark requirements for anti-plagiarism; to model process of procurement and detection of plagiarism process in public universities in Uganda; to examine how the challenges of Inter-Repository Plagiarism was addressed at Gulu University. The study reviewed existing literature on plagiarism policies in higher education institutions worldwide. The findings were that universities have varying views on levels of plagiarism with some policies allowing as high as 30% plagiarism level in scholarly work. Most of the peer-reviewed journals demand much lower allowable levels of plagiarism to encourage originality and sustainable adherence to copyright and intellectual property policies